Isolation and characterization of amylolytic, pectinolytic and cellulolytic microorganisms from local hotspring - Nurfarahin, Binti Jainuddin (Universiti Malaysia Sarawak (UNIMAS), 2013)
Thennophilic enzymes produces by microorganisms such as fungi has a very high potential in the industry. The objectives of this research study are to isolate and characterize amylolytic, pectinolytic and cellulolytic indigenous microorganism (in particular fungi) from local hot spring. Sampling was done at Kampung Panchor Dayak Hotspring by which two thenno tolerant fungal strains were successfully isolated. The fungal strains were named as FO I and F02. Screening test employed shows that both of the fungal strains have the ability to degrade starch, pectin and cellulose. Qualitative screening was done by supplementing citrus pectin, soluble starch and also carboxymethy1cellulose (CMC) separately as a substrate and there were halo region observed in both fungal strains culture in the supplemented agar plates after the application of iodine solution. As for quantitative screening test, sago 'hampas' was utilized as the substrate for the fungal strains to produce crude enzyme by which to be used for enzyme activity test using DNS method. Both screening test indicates that strain F02 produce high amount of cellulose (0.1943 U/mL) and pectinase (0.2058 U/mL). However, F02 identification was not done due to some limitation. Morphology characterisation shows that strain FOI was related to Apergillus sp. and identification through sequencing analysis showed that strain FOI was actually Aspergillus jitmigatus strain DF7 _ F 18S ribosomal RNA gene, 99% similarity.